WALLABY Early Science – II. The NGC 7232 galaxy group. Issue 4 (5th January 2019) - Lee-Waddell, K; Koribalski, B S; Westmeier, T; Elagali, A; For, B-Q; Kleiner, D; Madrid, J P; Popping, A; Reynolds, T N; Rhee, J; Serra, P; Shao, L; et al.
Abstract: We report on neutral hydrogen (H i ) observations of the NGC 7232 group with the Australian Square Kilometre Array Pathfinder (ASKAP). These observations were conducted as part of the Wide-field ASKAP L-Band Legacy All-sky Blind surveY (WALLABY) Early Science program with an array of 12 ASKAP antennas equipped with Phased Array Feeds, which were used to form 36 beams to map a field of view of 30 deg 2 . Analysing a subregion of the central beams, we detect 17 H i sources. Eleven of these detections are identified as galaxies and have stellar counterparts, of which five are newly resolved H i galaxy sources. The other six detections appear to be tidal debris in the form of H i clouds that are associated with the central triplet, NGC 7232/3, comprising the spiral galaxies NGC 7232, NGC 7232B, and NGC 7233. One of these H i clouds has a mass of MH i ∼ 3 × 10 8 M⊙ and could be the progenitor of a long-lived tidal dwarf galaxy. The remaining H i clouds are likely transient tidal knots that are possibly part of a diffuse tidal bridge between NGC 7232/3 and another group member, the lenticular galaxy IC 5181.